2007
DOI: 10.1111/j.1742-7843.2007.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Down‐Regulation of α1‐Adrenoceptor Expression by Lipid‐Soluble Smoke Particles through Transcriptional Factor Nuclear Factor‐κB Pathway

Abstract: Smoking is a strong risk factor for cardiovascular disease that is a leading cause of death and disability in Western countries. The present study was designed to investigate the effect of lipid-soluble smoke particles (DSP) on α -adrenoceptor expression in organ culture of rat mesenteric arteries and human epiploon arteries. Myograph and real-time reverse transcription-polymerase chain reaction were employed to assess vascular smooth muscle contractibility and the receptor mRNA expression in the smooth muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…found that this study is the first to demonstrate that lipid‐soluable smoke particles inhibit the contractile response of arteries in rat and human beings to down‐regulate the expression of G‐protein coupled family in vascular smooth muscle cells. This down‐regulation occurs via transcription and requires activation of intracellular NF‐κB signal pathway, which is an important inflammatory signalling .…”
Section: Discussionmentioning
confidence: 99%
“…found that this study is the first to demonstrate that lipid‐soluable smoke particles inhibit the contractile response of arteries in rat and human beings to down‐regulate the expression of G‐protein coupled family in vascular smooth muscle cells. This down‐regulation occurs via transcription and requires activation of intracellular NF‐κB signal pathway, which is an important inflammatory signalling .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the ETB2 receptor, the alteration of G-protein coupled receptors (GPCRs) like thromboxane A2 receptors and α1A-adrenoceptors (Zhang et al, 2007) in the VSMC has been studied under pathophysiological conditions. These findings along with additional clinical and experimental data provided the importance of the alteration of GPCRs in the pathogenesis of atherosclerotic CVDs, for their capabilities in regulating vascular tone and VSMC proliferation, which result in structure changes in the vascular wall associated with adverse remodeling, plaque formation, and in clinical sequelae such as myocardial infarction, stroke, and ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…5,26,27 OxS has been implicated in the etiology of several diseases linked to exposure to environmental toxicants, including PM, due to the increment of ROS concentrations that exceed antioxidant defenses and oxidase macromolecules. [30][31][32][33] Protein carbonylation is an irreversible, nonenzymatic process that results in the introduction of carbonyl groups into the protein molecule, leading to changes in its conformation. Protein carbonylation has been associated with the development of cardiovascular and respiratory diseases 34,35 and has been used as a biomarker of oxidized proteins.…”
Section: Lung Oxs and Dna Damagementioning
confidence: 99%